Soil moisture conservation agro-techniques for rainfed rabi sorghum - Patil, J V; Mishra, J S; Chapke, R R; Gadakh, S R; Chavan, U D (Indian Farming, 2015)
Rabi sorghum is a premium crop in states of Maharashtra, Karnataka and parts of Andhra Pradesh. It is primarily grown for foodgrain and fodder purposes. The productivity is low as the crop is grown on conserved soil moisture and faces terminal drought. In-situ moisture conservation practices like compartmental bunding and ridges and furrows, adoption of soil-based improved cultivars, nutrient management and irrigation scheduling based on water availability are the important management options for improving rabi sorghum productivity. Compartmental bunding during kharifseason conserved 12.6% more soil moisture and produced 20.6% higher grain yield over farmers’ practice. Soybean-rabi sorghum is the most productive and profitable cropping sequence.